2021
DOI: 10.3892/mmr.2021.12104
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA BANCR promotes proliferation, invasion and migration in esophageal squamous cell carcinoma cells via the Raf/MEK/ERK signaling pathway

Abstract: Esophageal squamous cell carcinoma (ESCC) is a major histological type of esophageal cancer, identified as a leading cause of tumor-associated death worldwide. In addition, long non-coding RNA (lncRNA) BRAF-activated non-coding RNA (BANCR) expression is increased in the plasma of patients with ESCC, which can be reversed by tumor resection. Thus, the aim of the present study was to investigate the underlying mechanism of BANCR in ESCC progression. The relative mRNA expression of BANCR was determined via revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In this study, we have focused on BANCR as a potential therapeutic target for human pancreatic cancer. In fact, there is increasing evidence that BANCR is overexpressed in human cancers, such as esophageal squamous cell carcinoma [23] and breast cancer [24]. BANCR is also upregulated in colorectal cancer plasma samples [25], and BANCR knockdown suppressed colorectal cancer progression and strengthened the chemosensitization of colorectal cancer cells to adriamycin [26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have focused on BANCR as a potential therapeutic target for human pancreatic cancer. In fact, there is increasing evidence that BANCR is overexpressed in human cancers, such as esophageal squamous cell carcinoma [23] and breast cancer [24]. BANCR is also upregulated in colorectal cancer plasma samples [25], and BANCR knockdown suppressed colorectal cancer progression and strengthened the chemosensitization of colorectal cancer cells to adriamycin [26].…”
Section: Discussionmentioning
confidence: 99%
“…manipulated an investigation to manufacture BANCR in esophageal squamous cell carcinoma (ESCC) cell lines; the assessment indicated that the overexpression of BANCR promoted the proliferation, migration, and invasion of ESCC cells through activation of the Raf/MEK/ERK signaling pathway. [ 40 ] Sadeghpour et al . conducted another investigation on the alteration of BANCR expression in ESCC patients; analysis showed the evaluation of BANCR expression associated closely with tumor differentiation and lymph node metastasis in ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are known to exert modulatory effects in diverse cancers via distinct molecular mechanisms, such as the interplay between lncRNAs and RNA‐binding proteins, including transcription factors 22 . For instance, lncRNA BANCR fosters ESCC cell invasive, proliferative, and migrating properties through the Raf/MEK/ERK pathway 23 . LncRNA NMR boosts ESCC cell migrating and invasive properties by interacting with the bromodomain PHD finger transcription factor 24 …”
Section: Discussionmentioning
confidence: 99%